Development of a High-Throughput Screening Assay to Identify Inhibitors of the Lipid Kinase PIP5K1C. (June 2015) - Wright, Brittany D.; Simpson, Catherine; Stashko, Michael; Kireev, Dmitri; Hull-Ryde, Emily A.; Zylka, Mark J.; Janzen, William P.
Phosphatidylinositol 4-phosphate 5-kinases (PIP5Ks) regulate a variety of cellular processes, including signaling through G protein-coupled receptors (GPCRs), endocytosis, exocytosis, and cell migration. These lipid kinases synthesize phosphatidylinositol 4, 5-bisphosphate (PIP2 ) from phosphatidylinositol 4-phosphate [PI(4)P]. Because small-molecule inhibitors of these lipid kinases did not exist, molecular and genetic approaches were predominantly used to study PIP5K1 regulation of these cellular processes. Moreover, standard radioisotope-based lipid kinase assays cannot be easily adapted for high-throughput screening. Here, we report a novel, high-throughput, microfluidic mobility shift assay to identify inhibitors of PIP5K1C. This assay uses fluorescently labeled phosphatidylinositol 4-phosphate as the substrate and recombinant human PIP5K1C. Our assay exhibited high reproducibility, had a calculated adenosine triphosphate Michaelis constant (Km) of 15 µM, performed with z' values >0.7, and was used to screen a kinase-focused library of 4700 compounds. From this screen, we identified several potent inhibitors of PIP5K1C, including UNC3230, a compound that we recently found can reduce nociceptive sensitization in animal models of chronic pain. This novel assay will allow continued drug discovery efforts for PIP5K1C and can be adapted easily to screen additional lipid kinases.